End of a mystery: Integrative approach reveals the phylogenetic position of an enigmatic Antarctic tardigrade genus Ramajendas (Tardigrada, Eutardigrada) - Tumanov, Denis V. (Zoologica scripta, 2022)
Phylogenetic position of the enigmatic Antarctic tardigrade genus Ramajendas was clarified using specimens from King George Island, Antarctic. Molecular phylogenetic analysis revealed a close affinity of Ramajendas to the superfamily Isohypsibioidea. At the same time, its standalone position within this clade prompted the erection of a new family Ramajendidae fam. nov. A detailed morphological description of the available specimens is given, and the diagnosis of the genus Ramajendas is amended. Taxonomical status of several previous findings of Ramajendas spp. in West Antarctica is discussed.